KLF9 Is a prognostic indicator in human pancreatic ductal adenocarcinoma - Mao, Zhengfa; Michalski, Christoph (Anticancer research, 2017)
Background: The aim of this study was to investigate the expression of Krüppel-like factor 9 (KLF9) and its clinicopathological significance and prognostic value in pancreatic ductal adenocarcinoma. Patients and Methods: A total of 149 patients diagnosed with pancreatic ductal adenocarcinoma who underwent curative surgery were enrolled in this study. The expression of KLF9 was examined immunohistochemically. The correlation of KLF9 with clinicopathological parameters and overall survival rate of patients were analyzed. Results: Low expression of KLF9 was observed in 62.82% of tumors, which was related to poor differentiation (p=0.036) and vascular invasion (p=0.017). Furthermore, the overall survival of patients with low KLF9 expression was significantly shorter than that of those with high KLF9 expression (p=0.001). Multivariate analysis confirmed KLF9 as an independent prognostic factor (p=0.000). Conclusion: KLF9 expression was found to be a valuable prognostic factor for patients with pancreatic ductal adenocarcinoma.